Preparation method of multi-coating stainless steel bipolar plate and application of multi-coating stainless steel bipolar plate in proton exchange membrane fuel cell

By depositing multi-layer TIACR1-A/TIBCR1-BNXOY coating on stainless steel bipolar boards, the problem of easily corrosion and electrical resistance in the metal bipolar board in fuel cells has been solved, and efficient corrosion resistance and conductive performance improvement has been achieved.

CN119381472AActive Publication Date: 2025-01-28SICHUAN UNIV

Patent Information

Application Number
CN202411494156.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing metal bipolar plates are prone to electrochemical corrosion in the acidic environment of proton exchange membrane fuel cells, and may lead to surface passivation and reduced conductivity in oxygen-rich environments, resulting in unsatisfactory corrosion resistance and conductivity.

Method used

Multi-curved ion plating technology is used to deposit multi-layer TIACR1-A/TIBCR1-BNXOY coating on the surface of the stainless steel substrate. The coating structure of the coating structure of the alternate cycle to form a uniform, dense, and high-adhesive coating to improve the corrosion resistance and corrosion ability and corrosion Conductive performance.

Benefits of technology

A significant reduction of corrosion current density, improvement of corrosion resistance and conductive performance, enhance the stability of the coating, and meet the performance requirements under the working conditions of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381472A_ABST
    Figure CN119381472A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, and discloses a preparation method of a multi-layer coating stainless steel bipolar plate and application of the multi-layer coating stainless steel bipolar plate in a proton exchange membrane fuel cell, the multi-layer coating stainless steel bipolar plate comprises a stainless steel substrate and a TiaCr1-a / TibCr1-bNxOy multi-layer plating layer arranged on the surface of the stainless steel substrate; wherein 0.10 < = a < = 0.24, 0.17 < = b < = 0.36, 1.02 < = x < = 1.08, and 0.17 < = y < = 0.21. According to the technical scheme, the corrosion resistance and the acid corrosion resistance of the modified stainless steel bipolar plate are remarkably improved, meanwhile, the interface contact resistance value between the bipolar plate and the gas diffusion layer is remarkably reduced, and the problem that an existing coated bipolar plate is not ideal in corrosion resistance and conductivity is solved. The stainless steel bipolar plate with the modified surface can be applied to a proton exchange membrane fuel cell, the performance of the device is improved, the stainless steel bipolar plate is suitable for batch production, and a large amount of cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for preparing a multi-layer coated stainless steel bipolar plate and an application thereof in a proton exchange membrane fuel cell. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) have attracted global attention for their outstanding advantages such as high power density, low operating temperature, low noise, and especially zero emissions. They are expected to play an important role in future social development and energy consumption reduction, and have great application prospects in electric vehicles, portable generators, micro aircraft, and various energy storage systems. As one of the key components of PEMFC, bipolar plates play an irreplaceable role in separating single cells, distributing reactant gases, conducting current, removing heat and moisture, etc. In addition, bipolar plates usually account for at least 70% of the total battery stack weight and volume, and about 20% of the total battery stack cost. Therefore, it is very important to promote the commercialization of PEMFC by developing low-cost, lightweight and highly reliable bipolar plates. The ideal bipolar plate must have good machinability, strong mechanical properties, and excellent corrosion resistance and electrical conductivity.

[0003] Graphite-based bipolar plates have good electrical conductivity and corrosion resistance, but they have deficiencies in mechanical strength, air permeability and manufacturing cost, which limit their large-scale industrial production. Metals and their alloy materials have high specific strength, good processing performance, strong thermal and electrical conductivity, and low preparation cost, making them ideal bipolar plate matrix materials. However, in the high temperature, humid and acidic working environment of proton exchange membrane fuel cells, however, in the working environment of proton exchange membrane fuel cells (such as low pH, high humidity, and operating temperature of about 80°C), low-cost metal bipolar plates such as stainless steel and titanium have both oxidizing and reducing media. On the anode side, the metal bipolar plate may slowly undergo electrochemical corrosion, and the multivalent cations generated by corrosion may diffuse into the proton exchange membrane, causing the proton conductivity of the membrane to decrease; on the cathode side, the bipolar plate may passivate on the surface in an oxygen-rich environment, causing an increase in surface contact resistance. Therefore, the application of metal bipolar plates must solve two problems: one is the electrochemical corrosion problem in the acidic system of proton exchange membrane fuel cells; the other is the problem of reduced conductivity caused by passivation on the metal surface. In response to the above problems, it is very important to develop protective coatings and their preparation methods that are both corrosion-resistant and highly conductive, which are the key to the application of metal bipolar plates in fuel cells.

[0004] In actual operation, by preparing a coating on the surface of a metal bipolar plate, the corrosion resistance and electrical conductivity can be effectively improved. Compared with a single-layer coating, a multilayer coating is more conducive to the improvement of the performance of the bipolar plate, and can reduce the presence of pinholes, large particles, or columnar crystals in the coating, thereby enhancing the stability of the coating. Wang Yanli et al. first prepared an organic carbon layer on stainless steel by using a segmented annealing treatment, and then used a disproportionation reaction to prepare a TiC coating in a molten salt, and finally obtained a continuous and dense TiC coating. (Application publication number: CN115491675 Multilayer gradient coating Cr / CrN / (Ti,W)3AlC2 for hydrogen fuel cell metal bipolar plates and its construction method). Although the obtained TiC coating is complete and dense, the corrosion resistance and electrical conductivity under fuel cell working conditions have not been reported. Zheng Lili and others prepared a multilayer gradient coating on the surface of a stainless steel substrate by magnetron sputtering and arc particle technology, with Cr as the transition layer, CrN as the connecting layer, and (Ti, W)3AlC2 as the outer layer (application publication number: CN116536626 A surface modification method for thin titanium bipolar plates of proton exchange membrane fuel cells). The coating preparation process is relatively complicated. Although the multilayer coating was successfully obtained, the corrosion resistance and conductivity of the coating are not ideal. Under simulated fuel cell operating conditions (80°C, 0.5mol / L H2SO4+2ppmHF), the corrosion current density after coating reached 0.78μA / cm 2 , contact resistance reaches 8.25mΩ·cm 2 .

[0005] Li Huanming et al. prepared a multilayer coating of metal inner layer (Au, Ag, Pt) / transition layer (one or more of Ti, Cr, Nb, Ta, W, Mo, C, N, Si) / interface diffusion layer (carbide or nitride of Ti, Cr, Nb, Ta, W, Mo, or non-metallic C, Si) / surface conductive layer (Au, Ag, Pt) on the surface of stainless steel (Application Publication No.: CN 112795886 A A conductive corrosion-resistant pre-coating for metal bipolar plate forming and its preparation method). The corrosion current density of the prepared Ti / TiN / C coating is 4.5×10 -5 A / cm 2 (1.6V vs.SCE, 10h), under a compression force of 0.6MPa, the interfacial contact resistance between the coating and carbon paper is 3.8mΩ·cm 2 Although the coating has good electrical conductivity, its corrosion resistance does not meet the DOE standard (corrosion current density <1.0μA / cm 2Hou Ming et al. prepared a transition layer (one or more of Cr, Ti, Ni, Cu, Al, V, Co, Ag, Au) / outermost layer (one or more of Cr, Ti, Ni, Al, V metal nitride) coating on the surface of stainless steel by ion plating. The corrosion current density of the modified coating is 0.12μA / cm 2 Under a compression force of 1.4 MPa, the interfacial contact resistance between the coating and carbon paper is 5.17 mΩ·cm 2 (Application publication number: CN 106684394 A A method for surface modification of stainless steel bipolar plates for proton exchange membrane fuel cells); however, cracks exist on the surface of the prepared coating, which reduces the stability of the coating under service conditions.

[0006] As can be seen from the above, the existing multi-layer coating preparation technology still has shortcomings such as complex preparation process, insufficient coating density, low corrosion resistance or conductivity, or insufficient stability. Summary of the invention

[0007] The present invention is intended to provide a method for preparing a multi-layer coated stainless steel bipolar plate and its application in a proton exchange membrane fuel cell to solve the technical problems of unsatisfactory corrosion resistance and conductivity of the bipolar plate.

[0008] To achieve the above object, the present invention adopts the following technical solution: a multi-layer coated stainless steel bipolar plate, comprising a stainless steel substrate and a Ti a Cr 1-a / Ti b Cr 1-b N x O y Multilayer coating; wherein 0.10≤a≤0.24, 0.17≤b≤0.36, 1.02≤x≤1.08, 0.17≤y≤0.21.

[0009] Preferably, as an improvement, multilayer Ti a Cr 1-a / Ti b Cr 1-b N x O y The overall thickness of the coating is 2.95-4.59 μm.

[0010] In this technical solution, the prepared multilayer Ti a Cr 1-a / Ti b Cr 1-b N x O y The thickness of the coating is between 2.95-4.59μm, which can achieve a relatively ideal anti-corrosion effect.

[0011] Preferably, the improved stainless steel substrate is a 316L stainless steel sheet.

[0012] In this technician's solution, among various metal materials, stainless steel, especially 316L stainless steel, has been widely used due to its excellent mechanical properties and low cost. In addition, 316L stainless steel contains about 2at% molybdenum, which makes it have better corrosion resistance than other austenitic or ferritic stainless steels.

[0013] Preferably, as an improvement, a method for preparing a multi-layer coated stainless steel bipolar plate comprises the following steps:

[0014] S1: ultrasonically cleaning the stainless steel substrate to obtain a pretreated stainless steel substrate;

[0015] S2: sputter cleaning the pretreated stainless steel substrate to obtain a stainless steel substrate to be coated;

[0016] S3: Multi-arc ion plating technology is used to deposit multi-layer TiCr / Ti on the surface of the stainless steel substrate to be coated. a Cr 1-a N x O y Plating.

[0017] Preferably, as an improvement, in S1, the specific operation of ultrasonic cleaning is: ultrasonically cleaning the stainless steel substrate with acetone and anhydrous ethanol for 30 minutes each in sequence.

[0018] In the technical solution, impurities on the surface of the stainless steel substrate, especially oil impurities, can be removed by ultrasonic cleaning; in addition, acetone and anhydrous ethanol are used for cleaning in sequence to ensure the cleaning effect.

[0019] Preferably, as an improvement, in S1, drying treatment is performed after ultrasonic cleaning, and the drying condition is vacuum drying at 80°C.

[0020] In the present technical solution, vacuum drying is adopted to achieve high drying efficiency at a relatively low temperature, which can effectively reduce the stress concentration phenomenon caused by the temperature gradient inside the material, avoid deformation or cracking of the material during the drying process, and thus reduce thermal damage to the material; and vacuum drying can reduce the pollution of dust and particulate impurities in the outside air to the material.

[0021] Preferably, as an improvement, in S2, the specific operation of sputtering cleaning is: placing the stainless steel substrate into the reaction chamber, adjusting the vacuum degree of the reaction chamber to 4.0-9.0×10 -3Pa; then argon gas is introduced into the reaction chamber and the pressure in the reaction chamber is maintained at 1Pa; the DC bias voltage of the substrate for sputtering cleaning is -300 to -200V, the time is 20 to 30min, and the target arc current is 80A to 100A.

[0022] In the technical solution, the substrate surface is first sputtered and cleaned before coating to remove the oxide film on the surface of the stainless steel substrate, and at the same time, the surface roughness of the titanium substrate is increased to improve the bonding strength with the coating.

[0023] Preferably, as an improvement, in S3, a multilayer Ti is deposited on the surface of the stainless steel substrate to be coated. a Cr 1-a / Ti b Cr 1-b N x O y The coating method is as follows: nitrogen is introduced into the reaction chamber to maintain the pressure in the reaction chamber at 3 Pa; a titanium target and / or a chromium target is used as a target material, an arc current is controlled to be 120 A, a substrate DC bias voltage is -90 V to -130 V, a transition layer TiCr layer is sputtered for 1 to 8 min, and Ti is sputtered. a Cr 1-a / Ti b Cr 1-b N x O y The total energy of the multiple layers is 300Ah, and different cycles are alternated in sequence, and the alternating different cycles are 4 cycles and 8 cycles respectively.

[0024] In this technical solution, the increase of the alternating cycle, Ti a Cr 1-a / Ti b Cr 1-b N x O y There are more interfaces in the multilayer coating, the thickness of the middle layer is thinner, and the diameter of the columnar structure in the coating decreases as the coating thickness becomes thinner. In addition, the increase in interfaces is conducive to the possible clogging of pinholes or columnar structures, the number of penetrating corrosion channels is significantly reduced, and the corrosion resistance of the bipolar plate is effectively improved. The test results of the corrosion resistance under the test conditions of 0.5M H2SO4+2ppm HF and 80℃ show that the corrosion resistance of the bipolar plate obtained using an alternating cycle of 8 cycles is the most ideal.

[0025] Preferably, as an improvement, in S3, the lattice mismatch between the TiCr transition layer and the stainless steel substrate is less than 6%.

[0026] In this technical solution, control Ti a Cr 1-a The lattice mismatch with stainless steel and the use of alternating energy bombardment are beneficial to suppress Ti aCr 1-a / Ti b Cr 1-b N x O y The porosity of the outer layer makes the multilayer Ti a Cr 1-a / Ti b Cr 1-b N x O y The coating is more compact. The inventors have found through a large number of experiments that controlling Ti a Cr 1-a When the lattice mismatch with stainless steel is less than 6%, the corrosion resistance of the coating is effectively improved.

[0027] Preferably, as an improvement, a multi-layer coated stainless steel bipolar plate is used in the preparation of a proton exchange membrane fuel cell.

[0028] In this technical solution, a multi-arc ion plating technology with a high deposition rate is used to deposit TiCr transition layer and TiCrN on the stainless steel bipolar plate. x O y layer, and then adopt an alternating cycle strategy to modulate the structure of the multilayer coating to obtain a uniform, dense, and highly adhesive coating. The reduction in thickness between each layer can inhibit the formation of columnar structures. In addition, the dense surface structure of the multilayer coating reduces the probability of defect formation, the transition layer forms a stable interface barrier, and the multilayer structure can block the grain boundaries in the columnar structure, eliminating the formation of pores, and effectively improving the corrosion resistance and post-corrosion conductivity of the stainless steel substrate. By optimizing the alternating cycles, the stability of the coating is significantly improved, including a significant reduction in corrosion current density, a reduction in long-term corrosion current density under constant potential, and a significant reduction in surface contact resistance attenuation. The overall coating has a fast preparation rate and an easy-to-control process, which can greatly improve the performance of the bipolar plate and thus increase the service life of the fuel cell.

[0029] In summary, the principle and advantages of this solution are: This technical solution adopts multi-arc ion plating technology to sputter multiple layers of Ti on the surface of the stainless steel substrate through DC reaction a Cr 1-a / Ti b Cr 1-b N x O y Coating (TiCr transition layer and TiCrN x O ylayer). Compared with stainless steel metal bipolar plates, the modified bipolar plates of this technical solution have a stable interface barrier formed by the transition layer, and the multi-layer structure can block the grain boundaries in the columnar structure, eliminating the formation of pores, and effectively improving the corrosion resistance and post-corrosion conductivity. By characterizing the surface morphology, corrosion resistance and conductivity of the prepared coating, it was found that a continuous and uniform structure was formed on the surface of the prepared coating. At 80°C, in a 0.5mol / L H2SO4+2ppmHF solution, air was introduced to simulate the working environment of PEMFC, and the corrosion current density was reduced to Ti by potentiodynamic polarization test. a Cr 1-a / Ti b Cr 1-b N x O y 0.047μA / cm of coating 2 At the same time, after a long-term constant potential (0.85V vs.SHE) polarization curve test, Ti a Cr 1-a / Ti b Cr 1-b N x O y The corrosion current density of the coating is as low as 0.055μA / cm 2 . At 140N / cm 2 Under the compression force of 100%, the interface contact resistance between the bipolar plate and the gas diffusion layer is as low as 4.8mΩ·cm 2 .

[0030] During the technical development, regulating the lattice mismatch between the TiCr layer and the stainless steel substrate is one of the keys affecting the coating performance. The inventors found during the research and development stage that the lower the lattice mismatch between TiCr and stainless steel, the better the TiCr layer will be. a Cr 1-a / Ti b Cr 1-b N x O y The lower the corrosion current density of the coating, the better the corrosion resistance. However, the lattice mismatch between TiCr and stainless steel is greatly affected by the composition and sputtering process. This technical solution uses a lot of research and development to adjust the distance between the sample and the target material and control the composition of TiCr. It is found that when the mismatch between the TiCr layer and stainless steel is <6%, the coating can also obtain excellent corrosion resistance. When the lattice mismatch between TiCr and stainless steel is 8.64% to 15.71%, it is difficult for the coating to obtain excellent corrosion resistance at the same time.

[0031] In addition, the number of coating layers and Ti b Cr 1-b N x O yThe control of layer thickness is another key technology that affects the performance of the coating. b Cr 1-b N x O y In order to ensure the efficiency of coating preparation, the total sputtering energy is set to 300Ah in the multilayer coating, and the total thickness of the coating is 2.95-4.59μm. The sputtering time of TiCr is 1min, and the thickness is controlled at about 0.03μm. In the research process, it was found that the number of alternations has a key influence on the coating thickness, corrosion current density and corrosion resistance stability, and the influence is nonlinear. When the number of alternations is 1, although Ti b Cr 1-b N x O y The layer thickness is relatively thick, reaching 2.92μm, and the corrosion current density is relatively high, reaching 0.185μA / cm 2 , but the long-term corrosion resistance is poor, and obvious corrosion holes appear on the surface after corrosion ( Figure 8 ). However, the more alternating times, the better. When the alternating times are high (16 times), the corrosion resistance current has been significantly improved, and the corrosion density has been significantly reduced to 0.072μA / cm 2 , good long-term corrosion resistance and stability, no obvious corrosion holes appear on the surface after corrosion ( Figure 8 ), but each layer of Ti b Cr 1-b N x O y The thickness of Ti is relatively thin, only 0.26μm. When the number of alternations is 8, b Cr 1- b N x O y The thickness is moderate, and the corrosion current density is significantly reduced to 0.047μA / cm 2 , and has good long-term corrosion resistance and stability, and no obvious corrosion holes appear on the surface after corrosion ( Figure 8 ).

[0032] This technical solution directly deposits multiple layers of Ti on the stainless steel substrate. a Cr 1-a / Ti b Cr 1-b N x O y coating, and control the transition layer composition to 0.10≤a≤0.24, Ti b Cr 1-b N x O yThe composition is 0.17≤b≤0.36, 1.02≤x≤1.08, 0.17≤y≤0.21, and the number of alternating cycles is controlled to be 4 to 8 cycles, so that excellent corrosion resistance and conductivity can be obtained at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the full XPS spectrum of Examples 1-2 and Comparative Examples 1-3 of the present invention.

[0034] Figure 2 The XRD spectra of Examples 1-2 and Comparative Examples 1-3 of the present invention are shown.

[0035] Figure 3 The SEM spectra of the surface-modified bipolar plates of Examples 1-2 and Comparative Examples 1-3 of the present invention are shown.

[0036] Figure 4 The cross-sectional SEM images of the surface-modified bipolar plates of Examples 1-2 and Comparative Examples 1-3 of the present invention are shown.

[0037] Figure 5 The potentiodynamic polarization curves of Examples 1-2 and Comparative Examples 1-3 of the present invention under a simulated 80°C PEMFC cathode working environment are shown.

[0038] Figure 6 The potentiodynamic polarization curves of Example 3 and Comparative Examples 4-7 of the present invention under a simulated 80°C PEMFC cathode working environment are shown.

[0039] Figure 7 The constant potential polarization curves of Example 2 and Comparative Example 1 of the present invention under a simulated 80° C. PEMFC cathode working environment are shown.

[0040] Figure 8 Surface SEM images of Example 2, Comparative Example 1 and Comparative Example 3 after constant potential polarization test of the present invention. DETAILED DESCRIPTION

[0041] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0042] Program Overview:

[0043] A multi-layer coated stainless steel bipolar plate, comprising a stainless steel substrate and a Ti a Cr 1-a / Ti b Cr 1-b N x Oy The stainless steel substrate is a 316L stainless steel sheet with a size of 27×27×0.1mm; the multilayer Ti a Cr 1-a / Ti b Cr 1-b N x O y The overall thickness of the coating is 2.95-4.59 μm.

[0044] A method for preparing a multi-layer coated stainless steel bipolar plate comprises the following steps:

[0045] S1: The stainless steel substrate is ultrasonically cleaned with acetone and anhydrous ethanol for 30 minutes each to remove grease on the surface of the stainless steel sheet, and then placed in a vacuum drying oven at 80°C for drying for standby use to obtain a pretreated stainless steel substrate;

[0046] S2: Sputter cleaning the pretreated stainless steel substrate to obtain a stainless steel substrate to be coated. The specific operation of sputter cleaning is: placing the pretreated stainless steel substrate into a reaction chamber, adjusting the vacuum degree of the reaction chamber to 4.0×10 -3 Pa; then argon gas is introduced into the reaction chamber, and the pressure in the reaction chamber is maintained at 1Pa; the DC bias voltage of the substrate for sputtering cleaning is -250V, the time is 30min, and the target arc current is 80A;

[0047] S3: Multi-arc ion plating technology is used to deposit multi-layer TiCr / Ti on the surface of the stainless steel substrate to be coated. a Cr 1-a N x O y The specific method is as follows: nitrogen is introduced into the reaction chamber to maintain the pressure in the reaction chamber at 3Pa; titanium target and / or chromium target are used as target materials, arc current is controlled to be 120A, substrate DC bias voltage is -100V, sputtering transition layer TiCr layer time is 1min, sputtering Ti a Cr 1-a / Ti b Cr 1-b N x O y The total energy of the multilayers is 300 Ah, and different cycles are alternated in sequence (the alternating different cycles are 4 cycles and 8 cycles in sequence), and the lattice mismatch between the TiCr transition layer and the stainless steel substrate is <6%.

[0048] A surface-modified stainless steel bipolar plate is used in a proton exchange membrane fuel cell.

[0049] Example 1

[0050] A method for preparing a multi-layer coated stainless steel bipolar plate comprises the following steps:

[0051] S1: A 316L stainless steel sheet (27×27×0.1 mm) was ultrasonically cleaned with acetone and anhydrous ethanol for 30 min each to remove grease on the surface of the stainless steel sheet, and then placed in a vacuum drying oven at 80°C for drying.

[0052] S2: Place the dried stainless steel sheet into the chamber of the multi-arc ion plating instrument, install a titanium target and a chromium target on the chamber, and close the chamber door. Then, vacuum the chamber to 4.0×10 -3 Pa, argon gas was introduced and the pressure in the chamber was maintained at 1Pa to sputter clean the surface of the stainless steel substrate (i.e. the surface of the stainless steel sheet). The target arc current was set to 80A and the substrate DC bias voltage was -250V during the sputter cleaning process. a Cr 1-a When the transition layer film is prepared, the sputtering time is 1 minute. b Cr 1-b N x O y When sputtering thin films, the total sputtering energy is 300Ah, alternating 4 times, the ion concentration in the cavity is uniform, the prepared thin film content is uniform, and there is no requirement for the target substrate distance.

[0053] S3: Using titanium target and chromium target as raw materials, a transition TiCr coating is deposited by DC reactive sputtering. The target arc current is set to 120A, the substrate DC bias voltage is -100V, and the sputtering time is 1 minute. Nitrogen is introduced, and Ti and chromium targets, nitrogen, and residual oxygen in the chamber are used as raw materials. b Cr 1-b N x O y During the deposition process, the nitrogen pressure was maintained at 3 Pa, the target arc current was set to 120 A, the substrate DC bias was -100 V, the total sputtering energy was 300 Ah, and the deposition was repeated 4 times.

[0054] After treatments S1 to S3, a surface-modified stainless steel bipolar plate is obtained, in which TiCr / Ti is modified on the upper and lower surfaces of the stainless steel substrate. a Cr 1-a N x O y Plating.

[0055] Example 2

[0056] The total sputtering energy of this embodiment is 300 Ah, and the sputtering time of the transition layer TiCr is 1 minute. The difference from Embodiment 1 is that in this embodiment, the alternating deposition is performed 8 times, and the energy of each alternating sputtering is 37.5 Ah.

[0057] Example 3

[0058] The total sputtering energy of this embodiment is 300 Ah, and the sputtering time of the transition layer TiCr is 1 minute. The difference from Embodiment 1 is that in this embodiment, alternating deposition is performed 4 times, and the energy of each alternating sputtering is 75 Ah.

[0059] Comparative Example 1

[0060] The total sputtering energy of this comparative example is 300 Ah, and the sputtering time of the transition layer TiCr is 1 minute. The difference from Example 1 is that the alternating deposition is performed once.

[0061] Comparative Example 2

[0062] The total sputtering energy of this comparative example is 300 Ah, and the sputtering time of the transition layer TiCr is 1 minute. The difference from Example 1 is that the deposition is performed alternately twice.

[0063] Comparative Example 3

[0064] The total sputtering energy of this comparative example is 300 Ah, and the sputtering time of the transition layer TiCr is 1 minute. The difference from Example 1 is that the alternating deposition is performed 16 times, and the energy of each alternating sputtering is 18.75 Ah.

[0065] Comparative Examples 4-7

[0066] Comparative Examples 4-7 are basically the same as Example 1, with a total sputtering energy of 300 Ah, a transition layer TiCr sputtering time of 1 minute, and 4 alternating depositions. The only difference from Example 1 is that during the deposition of the transition layer TiCr, the distance between the stainless steel substrate (stainless steel sheet) and the titanium target and the chromium target is changed, and the content of Ti and Cr elements is adjusted by adjusting the target distance. The specific settings of Comparative Examples 4-7 are shown in Table 1:

[0067] Table 1 Element contents of TiCr transition layers of Examples 1-3 and Comparative Examples 1-7

[0068]

[0069]

[0070] The element content and composition of the TiCr transition layer prepared in Examples 1-3 and Comparative Examples 1-7, the element content of the outermost layer and the film composition are shown in Table 2, wherein the relative content of the elements in the transition layer is calculated as follows: Ti = Ti (at.%) / (Ti (at.%) + Cr (at.%)); Cr = Cr (at.%) / (Ti (at.%) + Cr (at.%)); x = N (at.%) / (Ti (at.%) + Cr (at.%); y = O (at.%) / (Ti (at.%) + Cr (at.%)).

[0071] Table 2 Element content and composition of TiCr transition layer of Examples 1-3 and Comparative Examples 1-7

[0072]

[0073] From Table 1-2, it can be seen that the multilayer Ti prepared in Example 1 a Cr 1-a / Ti b Cr 1-b N x O y Coating, inner layer composition is Ti 0.24 Cr 0.76 , outer layer Ti b Cr 1-b N x O y The contents of Ti, Cr, N and O in the coating are 11.58 at.%, 32.99 at.%, 47.20 at.% and 8.23 ​​at.%, respectively. The composition of the film is Ti 0.24 Cr 0.76 / Ti 0.26 Cr 0.74 N 1.05 O 0.18 The eight-layer film prepared in Example 2 is composed of Ti 0.23 Cr 0.77 / Ti 0.17 Cr 0.83 N 1.08 O 0.21 The film prepared in Example 3 is composed of Ti 0.10 Cr 0.90 / Ti 0.18 Cr 0.82 N 1.02 O 0.17 The film composition prepared in Comparative Example 1 is Ti 0.25 Cr 0.75 / Ti 0.35 Cr 0.65 N 1.02 O 0.17 The film composition prepared in Comparative Example 2 is Ti0.25 Cr 0.75 / Ti 0.36 Cr 0.64 N 1.02 O 0.17 The film composition prepared in Comparative Example 2 is Ti 0.24 Cr 0.76 / Ti 0.42 Cr 0.58 N 1.02 O 0.15 The film composition prepared in Comparative Example 4 is Ti 0.79 Cr 0.21 / Ti 0.75 Cr 0.25 N 1.01 O 0.14 The film composition prepared in Comparative Example 5 is Ti 0.77 Cr 0.23 / Ti 0.61 Cr 0.39 N 1.02 O 0.12 The film composition prepared in Comparative Example 6 is Ti 0.66 Cr 0.34 / Ti 0.48 Cr 0.52 N 1.05 O 0.13 The film composition prepared in Comparative Example 7 is Ti 0.52 Cr 0.48 / Ti 0.36 Cr 0.64 N 1.3 O 0.12 .

[0074] Experimental Example 1

[0075] The lattice matching difference (lattice mismatch) between the TiCr layer prepared in Examples 1-3 and Comparative Examples 1-7 and the stainless steel substrate was tested, and the results are shown in Table 3:

[0076] Table 3 Lattice mismatch between the inner layer TiCr and the stainless steel substrate of Examples 1-3 and Comparative Examples 1-7

[0077] project Lattice mismatch Example 1 5.76% Example 2 5.25% Example 3 1.56% Comparative Example 1 5.85% Comparative Example 2 5.93% Comparative Example 3 5.58% Comparative Example 4 15.71% Comparative Example 5 12.62% Comparative Example 6 10.15% Comparative Example 7 8.64%

[0078] The formula for calculating the crystal mismatch is δ = (|d1–d2|) / d2, where δ is the lattice mismatch, d1 and d2 are the interplanar spacings of the substrate and coating, respectively. d1 is the (110) interplanar spacing of the stainless steel base layer, and d2 is the (311) interplanar spacing of the TiCr intermediate layer.

[0079] Experimental Example 2

[0080] The films prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to X-ray photon energy and X-ray diffraction analysis, and the results were as follows: Figure 1 , Figure 2 As shown. Figure 1 , Figure 2 It can be seen that the outermost layer of the coating of Example 1-3 forms a solid solution, which is preferentially oriented along the (111) crystal plane. The outermost layer of the coating of Comparative Example 1-2 also forms a solid solution, which is preferentially oriented along the (111) crystal plane.

[0081] Experimental Example 3

[0082] The surface modified bipolar plates of Examples 1-2 and Comparative Examples 1-3 were analyzed by scanning electron microscope. Figure 3 As shown. Figure 3 It can be seen that the surface of the coating prepared in Example 1-2 is smooth, the coating is tightly bonded to the titanium substrate, and the total thickness of the coating is 3.24 μm.

[0083] Experimental Example 4

[0084] The cross-sections of the surface-modified bipolar plates of Examples 1-2 and Comparative Examples 1-3 were analyzed by scanning electron microscopy. Figure 4 shown.

[0085] Experimental Example 5 Corrosion Performance Test

[0086] The bipolar plates prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to potentiodynamic polarization tests in a simulated PEMFC cathode working environment (0.5MH2SO4+2ppm HF, 80°C, air). Potentiodynamic polarization was performed using the Tafel plot test procedure. Within a certain voltage range, the test current changes with the potential. During the test, the scan rate was set to 0.3mV / s. The resulting curve is called a potentiodynamic polarization curve. The corrosion current can be calculated by the Tafel curve extrapolation method according to the formula (E corr =a+b Logi) is calculated, the linear part (Tafel zone) of the cathode and anode side curves is fitted and extended to intersect at one point. The potential corresponding to the intersection is the corrosion potential, and the corresponding current is the corrosion current. The test results are as follows Figure 5-7 As shown in Table 4. From the results, it can be seen that the corrosion potential and current density of the coating of Example 1 are 0.61V (vs. SHE) and 0.058μA / cm 2 The corrosion current density of Examples 1-3 is significantly lower than that of the comparative example. Moreover, since the lattice mismatch of Comparative Examples 4-7 is greater than 6%, the corrosion potential is significantly reduced and the corrosion current density is significantly increased.

[0087] Table 4 Test results of corrosion resistance of Examples 1-3 and Comparative Examples 1-7

[0088] project Corrosion Potential (V vs. SHE) <![CDATA[Corrosion current density (μA / cm 2 )]]> Example 1 0.610 0.058 Example 2 0.615 0.047 Example 3 0.605 0.078 Comparative Example 1 0.715 0.187 Comparative Example 2 0.645 0.153 Comparative Example 3 0.41 0.072 Comparative Example 4 0.045 2.678 Comparative Example 5 -0.26 1.955 Comparative Example 6 0.092 0.947 Comparative Example 7 -0.196 0.812

[0089] Experimental Example 6

[0090] The bipolar plates prepared in Example 2 and Comparative Example 1 were subjected to a constant potential polarization test in a simulated PEMFC cathode working environment (0.5MH2SO4+2ppm HF, 80°C, air). The constant potential polarization test was performed using an IT program, i.e., measuring the change of current over time at a constant potential, and was mainly used to study the stability and durability of the coating. The constant potential polarization test was performed in a simulated PEMFC cathode working environment for 10 hours. The results are shown in Figure 2. Figure 7 As shown, Figure 7 It can be seen that the corrosion current density of Comparative Example 1 is significantly higher than that of Example 2.

[0091] Experimental Example 7

[0092] After the constant potential polarization test, the surfaces of the bipolar plates of Example 2, Comparative Example 1 and Comparative Example 3 were analyzed by scanning electron microscope. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that no obvious corrosion holes appear on the coating surface of Example 2 after the test, while obvious corrosion holes appear on the coating surfaces of Comparative Examples 1 and 3 after the test.

[0093] Experimental Example 8 Surface Contact Resistance

[0094] The surface contact resistance of the coatings prepared in Examples 1-3 and Comparative Examples 1-7 was tested according to the test method in accordance with GB / T3048.16. The test results are shown in Table 5. As can be seen from the data in Table 5, the surface contact resistance of the coatings prepared in Examples 1-3 and Comparative Examples 1-7 is 0.0447 W / cm2 at 140 N / cm2. 2 The interfacial contact resistance between the coating and the carbon paper is 4.21~7.81mΩ·cm under the pressure of 2 , all meet the DOE2020 standard (ICR<10mΩ·cm 2 ).

[0095] Table 5

[0096] Group <![CDATA[Surface contact resistance (mΩ·cm 2 )]]> Example 1 4.80 Example 2 4.90 Example 3 7.81 Comparative Example 1 4.21 Comparative Example 2 4.53 Comparative Example 3 5.33 Comparative Example 4 4.21 Comparative Example 5 4.62 Comparative Example 6 5.16 Comparative Example 7 5.93

[0097] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A multi-layer coated stainless steel bipolar plate, characterized in that: It includes a stainless steel substrate and a Ti disposed on the surface of the stainless steel substrate. a Cr 1-a / Ti b Cr 1-b N x O y Multilayer coating; wherein 0.10≤a≤0.24, 0.17≤b≤0.36, 1.02≤x≤1.08, 0.17≤y≤0.

21.

2. The multi-layer coated stainless steel bipolar plate according to claim 1, characterized in that: Multilayer Ti a Cr 1-a / Ti b Cr 1-b N x O y The overall thickness of the coating is 2.95-4.59 μm.

3. The multi-layer coated stainless steel bipolar plate according to claim 2, characterized in that: The stainless steel substrate is a 316L stainless steel sheet.

4. The method for preparing a multi-layer coated stainless steel bipolar plate according to any one of claims 1 to 3, characterized in that: The steps include: S1: ultrasonically cleaning the stainless steel substrate to obtain a pretreated stainless steel substrate; S2: sputter cleaning the pretreated stainless steel substrate to obtain a stainless steel substrate to be coated; S3: Multi-arc ion plating technology is used to deposit multi-layer TiCr / Ti on the surface of the stainless steel substrate to be coated. a Cr 1-a N x O y Plating.

5. The method for preparing a multi-layer coated stainless steel bipolar plate according to claim 4, characterized in that: In S1, the specific operation of ultrasonic cleaning is: the stainless steel substrate is ultrasonically cleaned with acetone and anhydrous ethanol for 30 minutes each.

6. The method for preparing a multi-layer coated stainless steel bipolar plate according to claim 5, characterized in that: In S1, the ultrasonic cleaning is followed by drying, and the drying condition is vacuum drying at 80°C.

7. The method for preparing a multi-layer coated stainless steel bipolar plate according to claim 6, characterized in that: In S2, the specific operation of sputtering cleaning is as follows: placing the stainless steel substrate into the reaction chamber, adjusting the vacuum degree of the reaction chamber to 4.0-9.0×10 -3 Pa; then argon gas is introduced into the reaction chamber and the pressure in the reaction chamber is maintained at 1Pa; the DC bias voltage of the substrate for sputtering cleaning is -300 to -200V, the time is 20 to 30min, and the target arc current is 80A to 100A.

8. The method for preparing a multi-layer coated stainless steel bipolar plate according to claim 7, characterized in that: In S3, a multilayer Ti is deposited on the surface of the stainless steel substrate to be coated. a Cr 1-a / Ti b Cr 1-b N x O y The coating method is as follows: nitrogen is introduced into the reaction chamber to maintain the pressure in the reaction chamber at 3 Pa; a titanium target and / or a chromium target is used as a target material, an arc current is controlled to be 120 A, a substrate DC bias voltage is -90 V to -130 V, a transition layer TiCr layer is sputtered for 1 to 8 min, and a TiCr layer is sputtered. a Cr 1-a / Ti b Cr 1-b N x O y The total energy of the multiple layers is 300Ah, and different cycles are alternated in sequence, and the alternating different cycles are 4 cycles and 8 cycles respectively.

9. The method for preparing a multi-layer coated stainless steel bipolar plate according to claim 8, characterized in that: In S3, the lattice mismatch between the TiCr transition layer and the stainless steel matrix is ​​<6%.

10. Use of a multi-layer coated stainless steel bipolar plate according to any one of claims 1 to 3 in the preparation of a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Wear-resisting corrosion-resistant stainless steel color decoration protection coating and preparation method thereof

    CN104831232A

  • Surface-modified titanium bipolar plate, preparation method thereof and application of surface-modified titanium bipolar plate in proton exchange membrane fuel cell

    CN113675419A

  • Anti-corrosion coating of proton exchange membrane fuel cell, preparation method of anti-corrosion coating and fuel cell

    CN116154203A

  • Conductive corrosion-resistant coating for metal bipolar plate of fuel cell

    WO2020042535A1

Cited By

  • Porous transmission layer for proton exchange membrane water electrolysis cell as well as preparation method and application of porous transmission layer

    CN122522276A